El espejismo del Norte: los Geats y la pasión escandinava en la obra de Alejandro Busuioceanu - Felix Nicolau (Swedish Journal of Romanian Studies, 2023)
One of the less discussed figures of the Romanian exile caused by the fraudulent establishment of communism in Romania is the polygraph Alexandru Busuioceanu, who wrote poetry in three languages, but also art criticism, literary criticism, and history. The present research is interested in the ideational intertwining of Busuioceanu's intellectual life. As regards his poetry, the volume “Poemas patéticos” of 1948 is analyzed in particular. The writer formulated bold hypotheses which he justified with erudite arguments. Busuioceanu's research, like his art, was carried out in several countries, so access to sources and linguistic context was unmediated. The scholarly legacy of Vasile Pârvan, whose disciple Busuioceanu was, proved also important for this work. Has this enormous intellectual cargo and capacity imprinted Busuioceanu´s creativity or did he preserve his pristine imagination and thinking?